Pengaruh Pengendalian Persediaan Bahan Baku Dan Proses Produksi Terhadap Kualitas Produk Pada UMKM Warung Ohay: Studi Kasus Pada UMKM Warung Ohay Di Tasikmalaya - Indah Lupitasari; Suci Putri Lestari; Barin Barlian (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine the effect of controlling raw material inventory and production processes on product quality in MSMEs Warung Ohay Tasikmalaya. The type of research used is quantitative research. The population in this study was 40 employees of Warung Ohay MSMEs. The sampling technique in this study was saturated sampling of 40 employees. Data analysis in this study used multiple linear analysis with SPSS program version 25. The results of this study show that controlling raw material inventory and production processes simultaneously have a significant effect on the quality of Warung Ohay MSME products. Partial control of raw material inventory has a significant effect on the quality of Warung Ohay MSME products. The partial production process has a significant effect on the quality of Warung Ohay MSME products.